Implementation experience with MANET routing protocols. - Chin, Kwan-Wu (Computer communication review.)
This paper outlines our experience with the implementation and deployment of two MANET routing protocols on a five node, four hop, network. The work was prompted by the lack of published results concerning the issues associated with the implementation of MANET routing protocols on actual wireless networks, as opposed to results of simulation experiments. We examined implementations of two distance vector MANET routing protocols and found a number of problems with both protocols during the course of our experiments. The most significant was that neither protocol could provide a stable route over any multi-hop network connection. The route discovery process of both protocols is fooled by the transient availability of network links to nodes that were more than one hop away. Packets transmitted over a fading channel cause the routing protocol to conclude incorrectly that there is a new one hop neighbor that could provide a lower metric (hop count) route to even more distant nodes. This can occur even when nodes are stationary, mobility resulted in even less route stability. We implemented a simple signal strength based neighbor selection procedure to test our assertion that fading channels and unreliable network links were the cause of the failure of the routing protocols. The result was that neighbor discovery and the filtering for neighbors with which nodes could communicate reliably enables the creation of reliable multihop routes. Based on our experiences, we outline several recommendations for future work in MANET research.